Kinerja Keuangan dan Tata Kelola yang Baik: Pilar Pengungkapan Laporan Keberlanjutan - Dewi, Indah Permata; Aji, Nur Prasetyo; Ariani, Kurnia Rina (Jurnal Akuntansi dan Pajak, 2024)
This study aims to examine the effect of financial performance and corporate governance on sustainability report disclosure. Sustainability reports reflect a company's commitment to sustainable business practices in the environmental, social and economic fields. Financial performance is measured based on the company's ability to plan and implement profitable business strategies, while corporate governance involves processes, rules and policies that affect business entities. The object of this research is manufacturing companies that publish sustainability reports and annual reports on the Indonesia Stock Exchange (IDX) and the company's official website for the period 2020-2023. The data collection technique used purposive sampling method. The research results show that a high level of profitability encourages companies to report financial performance transparently. Higher leverage encourages increased disclosure of sustainability reports to maintain a positive image in the eyes of stakeholders. The independent board of commissioners plays an important role in ensuring the protection of majority and minority interests through social responsibility reporting. Low managerial ownership inhibits managers from maximizing company value through disclosing sustainability reports. The number of audit committees that are too large and frequent audit committee meetings can reduce the effectiveness of disclosure of sustainability reports.